Advancing sustainability-oriented innovation practice with quality criteria for problem definitions - Brooke Wilkerson (Heliyon)
Defining the problem is a key step in sustainability-oriented innovation (SOI), yet practitioners often have little guidance on what qualities a problem definition should or could have. This can result in problem definitions that are poorly specified or underdeveloped, which can negatively affect the quality of the innovation process and narrow sustainability impact.Drawing on innovation and sustainability science literature, this article first operationalizes the concept of sustainability for an innovation context and then proposes a list of quality criteria which can support development of a SOI problem definition and provide opportunities for critical reflection. Application of the quality criteria is illustrated in a case study. Results indicate that quality criteria can guide structured thinking and improve problem definition quality, but that some practitioners may meet a tradeoff between meeting all criteria and moving forward in the SOI process. This supports the role of quality criteria as a guidance and support tool rather than a tool for evaluation of problem definitions.